The Relationships Between Sport Specialization, Sleep, and Quality of Life in Female Youth Volleyball Athletes. (March 2022) - Watson, Andrew; McGuine, Timothy; Lang, Pamela; Post, Eric; Biese, Kevin; Kliethermes, Stephanie; Brooks, M. Alison; Bell, David
Background: Although sport specialization may be associated with stress and burnout among youth athletes, the relationship with quality of life (QOL) remains unknown. The purpose of this study was to evaluate the relationship between sport specialization, sleep, and QOL in female youth athletes. Hypothesis: Higher levels of specialization are associated with increased daytime sleepiness and worse QOL. Study Design: Cross-sectional study. Level of Evidence: Level 4. Methods: Female high school volleyball players completed preseason surveys to determine sport specialization (low, moderate, high), injury history, QOL, sleep duration, and daytime sleepiness. QOL and sleep variables were compared across specialization groups. Multivariable linear regression models were developed to evaluate the associations between sleepiness, QOL, specialization, grade in school, and injury history. Results: Of 1482 participants, 591 (40%), 436 (29%), and 455 (31%) were categorized as low, moderate, and high specialization, respectively. Highly specialized athletes demonstrated worse QOL (median 91.3 [interquartile range 86-96]) than low (92.4 [88-97], P = 0.05) and moderate (93.5 [88-99], P = 0.05) specialization groups and greater daytime sleepiness (11 [7-15]) than low (10 [6-14], P < 0.001) and moderate (10 [6-14], P < 0.001) specialization groups. In the multivariable model, QOL was negatively associated with prior injury occurrence (β = −1.1 ± 0.5, P = 0.02), but not grade in school (β = −0.08 ± 0.2, P = 0.71) or specialization (moderate: β = 0.08 ± 0.5, P = 0.88; high: β = −0.70 ± 0.5, P = 0.18). Daytime sleepiness increased with high specialization (β = 1.12 ± 0.3, P < 0.001) and grade (β = 0.76 ± 0.1, P < 0.001), but not prior injury (β = 0.51 ±0.3, P = 0.10). Conclusion: Highly specialized female volleyball athletes demonstrate decreased QOL, perhaps because of higher rates of prior injury. Specialization is also associated with increased daytime sleepiness. Clinical Relevance: Sport participation patterns and injury may have implications for QOL in youth athletes.